Study of blind and visually impaired individuals and their emotional relation with clothing brands - Pina, Liliana Maria Gonçalves (2022)
This research aims to understand the emotional relationship of visually impaired (VI) individuals with fashion brands. The research is divided into two parts based on a qualitative and exploratory methodology. Due to the lack of studies on this thematic and sample, the first part of the research corresponds to an extensive literature review described in five chapters: the visually impaired person, fashion design, inclusive design, consumer behaviour and fashion branding. The reading and interpreting processes were based in articles published in scientific journals, books, book chapters, magazines and websites. The second part of the research, the empirical part, is divided into two practical studies. First, to start the chapter, a case study of designers with clothing product development based on inclusive design and directed to people with VI was performed to support the methodology used. The further studies occurred in two temporal moments. The first technique and the first phase of data collection relied on in-depth interviews counted with the participation of a sample of 27 visually impaired individuals with distinct diagnoses (e.g., congenital blindness (CB), acquired blindness (AB) and partially sighted (PS). The interviews were conducted face-to-face, via telephone, and videoconference (e.g., zoom). The first two interviews were pilot tests. As modifications were made to the interview script after these two tests, a sample composed of 25 cases was considered for data analysis. The second study was based on the concept of "intraview". By developing a sensory tool composed of different textile samples, an activity was proposed that consisted of stimulating the tactile, olfactory and auditory senses of people with DV. In this case, the interview concept was reconceptualized, providing a dynamic activity centred on selecting several textile materials and different techniques and based on the exploration and interaction levels. The tool also assesses several solutions and, consequently, several accessibilities and social inclusion techniques. In this second study, in the 1st round of interviews, 5 participants were employed. Data collection was carried out face-to-face. In both studies, the choice of the participants was based on non-probabilist, purposive and convenience sampling. ACAPO association provided support as an intervener in enticing possible participants for the study. For the respective data analysis in both studies, NVivo software was used. The hierarchical coding system created in the software was based on a mixed-method, initially deductive and later inductive. Different tools were used for voice and image capture in both interviews and data collection phases. At each moment of data collection, two different scripts were used. A field diary was also employed in the second study, where considerations and comments given by participants were noted. This information was used to improve the design of the solutions presented and possible further validation with other VI samples. Through these two studies, it is possible to conclude that the brand value for the VI consumer focuses essentially on the fashion product, more specifically clothing. I.e., the brand element through which VI consumers create their associations and memories and how they remember the brands are materialized through the product. However, these associations and the limited knowledge that the consumer has of the product are not enough for this consumer to create an emotional relationship with the brand. Although a large part of the sample could relate emotionally to the brand, this is not enough to create a stronger relationship (e.g., attachment, passion, love) because they are not loyal to brands. It can be considered that the communication failures between the brand's products and the lack of the brand's social relationship with the VI consumer are the main reasons the person cannot get loyal to the fashion brand. Considering conventional clothing on sale in the national market, it was possible to specify reference brands and consumer preferences regarding garment design. In the inclusive design spectrum and product development, and to what is crucial for the fashion designer, it was possible to understand that the values associated with the VI consumer's product are essentially centred on the product's ability to provide tactile stimuli, on the quality of the materials and their manufacturing. There is a predisposition and interest in choosing technical, practical, and functional materials. The importance of verbal and audible communication between the product and the VI consumer was also proven. It is confirmed that audio description can be achieved by implementing technological solutions (Smartphone and QR Code). Brand strategies in terms of communicational accessibility should focus on the product without neglecting to implement a more careful and more sensitive assistance service for the disabled consumer. Besides, apart from the product by addressing other brand elements (e.g., product and brick and mortar store assistance and environment), this research brought a new and original context to the scientific fashion field. Therefore, it can be assumed that this research is an asset for designers and fashion brands interested in having a more accessible and inclusive approach to their strategies and business. It will be essential to disseminate the results among the research partners and make the document fully accessible for people with VI.